Hermeneutics a very short introduction - Zimmermann, Jens 1965- (Very short introductions, 2015)
This short introduction to hermeneutics demonstrates the central role of interpretation in our daily lives. By considering the historic developments in hermeneutic theory as well as its contemporary relevance, Zimmermann explains how humans continue to draw knowledge from the world around them